2019
DOI: 10.15171/joddd.2019.010
|View full text |Cite
|
Sign up to set email alerts
|

Color agreement between try-in paste and resin cement: Effect of thickness and regions of ultra-translucent multilayered zirconia veneers

Abstract: Background. The current study aimed at identifying the color agreement between try-in pastes and the respective resin cements and investigated the effect of thickness and regions of Ultra-Translucent Multilayered Zirconia Veneers. Methods. A total of 90 cubic zirconia discs were prepared at two different thicknesses (0.5 mm and 0.7 mm) (n=45) in five groups in terms of the shade of the try-in paste and resin cement as follows: Universal, Clear, Brown, White and Opaque. Try-in paste and the respective resin ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Daneshpooy et al 16 revealed colour differences in Panavia V5 resin cement among all shades (universal, clear, brown, white and opaque) of try-in paste and corresponding resin cement under ultra-translucent multi-layered zirconia veneers of two different thicknesses. Similar to the results of this study, the white 18 evaluated the relationship between try-in pastes and corresponding resin cement of different brands, and they concluded that colour differences were found in all shades and for all manufacturers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Daneshpooy et al 16 revealed colour differences in Panavia V5 resin cement among all shades (universal, clear, brown, white and opaque) of try-in paste and corresponding resin cement under ultra-translucent multi-layered zirconia veneers of two different thicknesses. Similar to the results of this study, the white 18 evaluated the relationship between try-in pastes and corresponding resin cement of different brands, and they concluded that colour differences were found in all shades and for all manufacturers.…”
Section: Discussionmentioning
confidence: 99%
“…Daneshpooy et al 16 . revealed colour differences in Panavia V5 resin cement among all shades (universal, clear, brown, white and opaque) of try‐in paste and corresponding resin cement under ultra‐translucent multi‐layered zirconia veneers of two different thicknesses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O efeito de espessuras menores da zircônia ultra translúcida, de 0,5 mm e 0,7 mm foi investigado por Daneshpooy et al 23 , a proposta do estudo foi avaliar a correspondência de cores entre as pastas try-in e os respectivos cimentos resinosos quando utilizado esta zircônia, assim como o efeito nas suas multicamadas. Para isso, cinco cores de cimento foram avaliadas e a cor foi mensurada em três regiões diferentes da amostra: cervical, média e incisal para cada camada de cerâmica, simultaneamente.…”
Section: Tabela 1 Classificação Das Zircôniasunclassified